2014
DOI: 10.4028/www.scientific.net/amr.874.9
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Diamond-Like Carbon Coatings

Abstract: The aim of the study was to analyze the superhard anti-wear diamond-like carbon coatings produced by Plasma Assisted Chemical Vapor Deposition (PACVD) and Physical Vapour Deposition (PVD). The a-C:H and a-C:H:W coatings were deposited on steel elements operating under friction conditions. The analysis involved comparing the tribological properties of coated metal elements with those of uncoated elements. It was essential to analyze how the coating composition and structure influence the tribological behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Based on research, among others, presented in [21], it was found that the coefficient of friction of an element with a coating made in a technology based on diamondcontaining layers is lower, especially in cooperation with steel and cast iron surfaces. Another extremely important feature of these coatings is wear resistance, manifested by its lower value, which was also found based on the presented research [14]. The use of these coatings becomes particularly important in the event of an intensification of loads, which is, for example, the case in the drive engines of diesel locomotives and inland waterway vessels.…”
Section: Discussionsupporting
confidence: 72%
“…Based on research, among others, presented in [21], it was found that the coefficient of friction of an element with a coating made in a technology based on diamondcontaining layers is lower, especially in cooperation with steel and cast iron surfaces. Another extremely important feature of these coatings is wear resistance, manifested by its lower value, which was also found based on the presented research [14]. The use of these coatings becomes particularly important in the event of an intensification of loads, which is, for example, the case in the drive engines of diesel locomotives and inland waterway vessels.…”
Section: Discussionsupporting
confidence: 72%
“…The adhesion of the coating to the Ti13Nb13Zr substrate was investigated using a scratch test. The test was carried out using an Anton Paar NHT 3 The test consisted in scratching the surface of the specimen with a Sphero-conical diamond indenter with a rounded radius of 2 µm at a load linearly increasing from 0.03 to 5 mN, a loading rate of 20 mN/min and a scratch length of 3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, for many years, research has been conducted on surface modification of biomaterials to protect metal ions from entering the patient's body. The most commonly considered are various types of surface layers and coatings produced by physical and chemical methods [2][3][4][5][6].…”
Section: Properties Of Tio2 Coatings Obtained By Atomic Layer Deposit...mentioning
confidence: 99%
“…In their investigation, Madej et al [174] explored the tribological properties of diamond-like carbon (DLC) coatings, specifically a-C:H and a-C:H:W, fabricated using plasma-assisted chemical vapor deposition (PACVD) and physical vapor deposition (PVD) methods. These superhard anti-wear coatings were applied to steel elements and subjected to scrutiny under both dry and ionic liquid lubricated conditions.…”
Section: Tribology Of Doped Diamond-like Carbon Coatings and Ionic Li...mentioning
confidence: 99%